Ryegrass (Lolium multiflorum) BRS Ponteio and wheat (Triticum aestivum) BRS Tarumã pasture with different doses of ammonium sulfate as topdressing - Luiz Carlos Timm; Ione Maria Pereira Haygert-Velho; Delvacir Rezende Bolke; Gustavo Veiverberg Antunes; Dileta Regina Moro Alessio; João Pedro Velho (Acta Scientiarum. Animal Sciences, 2019)
This study analyzed the behavior of the annual ryegrass (Lolium multiflorum) BRS Ponteio and dual-purpose wheat (Triticum aestivum) BRS Tarumã with different doses of ammonium sulfate as topdressing and evaluated the exponential growth model to explain the physiological development of both species. For each species, a completely randomized design was used with four replications per treatment with 9m2 area, in which the following treatments were distributed: 0, 150, 250, 350 and 450 kg nitrogen per hectare applied as ammonium sulfate. The cumulative and adjusted productions to the exponential growth model at the end of the cycle were, respectively: BRS Ponteio 150 = 5,620; 250 = 5,920; 350 = 7,585 and 450 = 8,491 and BRS Tarumã 150 = 3,922; 250 = 5,060; 350 = 7,024 and 450 = 7,491 kg dry matter per hectare. The cultivars analyzed without nitrogen application had limited growth and showed no adjustment even to the first order linear model. The application of nitrogen decreased the interval between cuts and increased dry matter production per hectare following the exponential growth model.